A new challenge in forensic toxicology exemplified by a case of murder under the influence of a synthetic cannabinoid – AM-2201 - Rojek, Sebastian; Kłys, Małgorzata; Maciów-Głąb, Martyna; Kula, Karol (Legal medicine (Tokyo, Japan), 2017)
[Display omitted] •Synthetic cannabinoids pose a new challenge to clinical and forensic toxicology.•The authentic case shows the toxic action of AM-2201 on the human body.•AM-2201 at concentration 0.48ng/ml in blood sample of murderer was revealed.•Additionally, THC-COOH at concentration 23ng/ml was determined. Among new psychoactive substances (NPS) available on the narcotic market, a significant number consists of synthetic cannabinoids commonly known as smokable herbal “spice” and “K2”, and which are legally treated as a legal alternative to marijuana. The dearth of information on the pharmacology of these intoxicants as they are introduced into the market has created the urgent need among healthcare providers for case studies on the substances belonging to this group, both in terms of the consequences of using such intoxicants, and in methods of detection. The subject of the present report is a multi-parameter analysis of a criminal case of an 18-year-old male who was charged with murder of his female relative and attempted murder of two other victims by stabbing. The defendant pleaded guilty, but he claimed that he had been acting without volition, because he was under the influence of the synthetic cannabinoid AM-2201, which had been purchased from a dealer as a 10g package labelled “Mr Green – No bad trip”. Analytical methods including gas chromatography – electron ionization – quadrupole ion trap mass spectrometry (GC-EI-QIT/MS) and liquid chromatography, electrospray ionization, tandem mass spectrometry (LC-ESI-MS-MS) were developed to determine the presence of AM-2201 in the Mr Green – No Bad Trip, and in the blood of the perpetrator, respectively. Toxicological findings are discussed in the context of psychoactive and adverse physical effects resulting from the presence of AM-2201 in the human body; the observations were also analyzed in conjunction with data from the literature.